GR_GERICHTE SK1 2019 47 vom 23. Februar 2022 , autorità parentale/istruzione/regolamentazione dei diritti di visita - GR Gerichte (2022)
gewerbsmässiger Betrug gemäss Art. 146 Abs. 2 StGB | StGB 137-172 Vermögen